Does acute maternal stress in pregnancy affect infant health outcomes? Examination of a large cohort of infants born after the terrorist attacks of September 11, 2001 - Conlin Ava Marie S; Sevick Carter J; Ryan Margaret AK; Endara Skye M; Macera Caroline A; Smith Tyler C (BMC, 2009)
Abstract Background Infants in utero during the terrorist attacks of September 11, 2001 may have been negatively affected by maternal stress. Studies to date have produced contradictory results. Methods Data for this retrospective cohort study were obtained from the Department of Defense Birth and Infant Health Registry and included up to 164,743 infants born to active-duty military families. Infants were considered exposed if they were in utero on September 11, 2001, while the referent group included infants gestating in the same period in the preceding and following year (2000 and 2002). We investigated the association of this acute stress during pregnancy with the infant health outcomes of male:female sex ratio, birth defects, preterm birth, and growth deficiencies in utero and in infancy. Results No difference in sex ratio was observed between infants in utero in the first trimester of pregnancy on September 11, 2001 and infants in the referent population. Examination of the relationship between first-trimester exposure and birth defects also revealed no significant associations. In adjusted multivariable models, neither preterm birth nor growth deficiencies were significantly associated with the maternal exposure to the stress of September 11 during pregnancy. Conclusion The findings from this large population-based study suggest that women who were pregnant during the terrorist attacks of September 11, 2001 had no increased risk of adverse infant health outcomes.